Determinación de la presencia de parásitos internos y externos en camélidos sudamericanos en la comunidad El Mirador de los Pastos Tulcán - Vaca Mora, Jimmy Alejandro (2025)
This research was conducted in the Tulcán Canton, González Suarez Parish, with the aim of determining the presence and impact of parasites in alpacas in the Mirador de los Pastos community. Fecal samples from 36 alpacas were collected to analyze internal parasites, and through observation, external parasites were detected before and after deworming treatment. An experimental design was not implemented; instead, descriptive statistics, chi-squared tests, and Tukey tests were used to analyze the data. The studied alpacas were classified by age (adults being the most frequent at 47.20%), and a higher number of females (69.40%) were observed than males. White was the predominant coat color (86.1%). After treatment, an improvement was observed in the body weight and physical condition of the alpacas in the different age groups. The initial coprological analysis revealed a 100% prevalence of internal parasites, with species such as Entamoeba coli, Nematodirus, Trichuris vulpis, and Toxocara spp. identified. The analysis after treatment showed a significant reduction in the frequency of these parasites, with an overall effectiveness of 80.5%. Risk factors such as contact with other animals, mosquitoes, poor facility management, water management, population density, feeding practices, stress, environmental conditions, and inadequate mosquito control were significantly associated with the incidence of parasites. No visible external parasites were detected. This research concluded that internal parasites negatively impact the health of alpacas in this community, highlighting the need for effective parasite control measures to ensure the well-being and productivity of the animals.